The pistachio prescription : a novel - Danziger, Paula, 1944-2004. (New York : Dell, 1978)
A high school "freshperson" attempts to rise above such inconveniences of life as her older sister, parents, and school.
Booklist.
School Library Journal.
Wilson's Junior High School.
5.1
5-8
7-9
Keywords: Family life -- Fiction; Schools -- Fiction; Family life -- Fiction; School stories